Unlocking academic success: the impact of teaching strategies, instructor support, and student innovation on learning outcomes in public administration - Waiphot Kulachai; Khwanta Benchakhan; Patipol Homyamyen (Cogent Education)
This study examines the impact of varied teaching activities, instructor support, and student innovation on learning outcomes for 233 Public Administration students at Suan Sunandha Rajabhat University. Data were gathered using structured online questionnaires, with Structural Equation Modelling in SmartPLS 4 used for analysis. Results indicate that diverse teaching methods, including simulations and group work, foster student creativity, while strong instructor support boosts creative problem-solving. These approaches lead to practical engagement, bridging theory with practice and fostering student-led innovation. Notably, student innovation did not mediate the relationship between teaching methods and learning outcomes, suggesting the need to explore other factors, like motivation or an optimal learning environment. Educators are encouraged to integrate simulations, group projects, and strong instructor support to enhance engagement and creativity, while institutions should invest in professional development and inclusive curricula to optimize learning outcomes. The study advocates for innovative teaching techniques and motivational approaches to expand learning potential and raise academic visibility for Public Administration students.